Synthesis of α,β-Unsaturated Phosphine Sulfides - Wang, Xian-Liang; Chen, Jin-Xiang; Jia, Xue-Shun; Yin, Liang (Synthesis, 2020)
α,β-Unsaturated phosphine sulfides may exhibit different reactivity from α,β-unsaturated phosphine oxides toward nucleophilic addition and thus may find new applications in copper(I)-catalyzed asymmetric reactions. Herein, various α,β-unsaturated phosphine sulfides were prepared in moderate to excellent yields from the parent α,β-unsaturated phosphine oxides with Lawesson’s reagent. The reaction enjoys a broad substrate scope and tolerates a variety of functional groups.
Keywords: phosphine oxides; phosphine sulfides; thionation; Lawesson’s reagent; thiocarbonyl compounds